2019
DOI: 10.1038/s41598-018-37730-0
|View full text |Cite
|
Sign up to set email alerts
|

SmvA is an important efflux pump for cationic biocides in Klebsiella pneumoniae and other Enterobacteriaceae

Abstract: The multidrug resistant (MDR) opportunistic pathogen Klebsiella pneumoniae has previously been shown to adapt to chlorhexidine by increasing expression of the MFS efflux pump smvA. Here we show that loss of the regulator SmvR, through adaptation to chlorhexidine, results in increased resistance to a number of cationic biocides in K. pneumoniae and other members of the Enterobacteriaceae. Clinical Enterobacteriaceae isolates which lack smvA and smvR also have an increased susceptibility to chlorhexidine. When s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
2
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 44 publications
2
51
2
1
Order By: Relevance
“…1 and Table 1). Recently, it has been shown that heterologous expression of smvA from K. pneumoniae or S. enterica in Escherichia coli (which does not possess smvAR homologs) modestly increased the MICs of CHX (from 0.5 to 2 to 4 mg/liter) (6). It is noteworthy that, in contrast to observations in these E. coli strains, we did not observe any growth defect for our ECC transconjugants (data not shown).…”
Section: Resultscontrasting
confidence: 51%
See 2 more Smart Citations
“…1 and Table 1). Recently, it has been shown that heterologous expression of smvA from K. pneumoniae or S. enterica in Escherichia coli (which does not possess smvAR homologs) modestly increased the MICs of CHX (from 0.5 to 2 to 4 mg/liter) (6). It is noteworthy that, in contrast to observations in these E. coli strains, we did not observe any growth defect for our ECC transconjugants (data not shown).…”
Section: Resultscontrasting
confidence: 51%
“…These data contrast with the absence of SmvR mutations in Enterobacter sp. upon CHX exposure while mutations have been observed in Klebsiella, Citrobacter, and Salmonella (6). Because one substitution (G52A) was present into one of the two highly conserved regions of the SmvR sequence in clinical isolates, it is tempting to speculate that it could play a role in high CHX MICs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biocides play an important role in infection control and are often used to remove microbes from equipment, surfaces, and skin prior to medical procedures (13). The rising incidence of multidrug resistance in nosocomial pathogens has further magnified the clinical value of biocides, and there is increasing reliance on these antimicrobials to reduce antibiotic usage through more effective infection control strategies (1, 46). However, despite their clinical significance, biocides are subject to far fewer regulations on their use than therapeutic agents, such as antibiotics (2).…”
Section: Introductionmentioning
confidence: 99%
“…The latter is evident in E. coli with the multiple antibiotic operon, Mar [ 106 , 123 ]. Furthermore, either direct mutations or mutations in the Tet-R family regulator of the MFS family efflux pump smvA in K. pneumoniae , P. mirabilis, E. cloacae and S. enterica serotype Typhimurium are associated with increased biocide resistance, including to chlorhexidine [ 124 , 125 , 126 ] and acriflavine [ 127 ]. Efflux pump regulatory pathways have been noted to be interwoven into many other regulatory processes that promote bacterial virulence such as biofilm formation, quorum sensing and membrane permeability [ 110 , 128 , 129 ].…”
Section: Efflux Pumpsmentioning
confidence: 99%